Trends in prostate cancer incidence and mortality in a mid-sized Northeastern Brazilian city - Lima,Carlos Anselmo (2013)
OBJECTIVE: International data have reported prostate cancer as the most frequent among men, and the third highest in mortality. A rise in incidence has been observed in the course of recent decades, probably influenced by early detection, mainly in asymptomatic men, through regular screening with prostate-specific antigen (PSA) testing. The purpose of this study was to contribute to information on trends in prostate cancer incidence and mortality using population-based data. METHODS: This was an exploratory ecological study of time trends, aiming at describing changes in prostate cancer incidence and mortality in Aracaju, Sergipe, Brazil, from 1996 to 2006. Rates were calculated from data of the Registro de Câncer de Base Populacional de Aracaju. Trends were calculated using the Joinpoint Regression Program. RESULTS: For the study period, 1,490 incident cases and 334 deaths were included. Incident cases were more common after 50 years of age, and deaths after 55 years. Age-standardized incidence rates of 46.6 and 50.0/100,000 were observed in the early years of the series, and then progressively increased, with rates higher than 100.0/100,000 in later years. For mortality, age-standardized rates varied from 21.6 and 16.6/100,000 to 24.1 and 28.9/100,000 in later years. Joinpoint analysis identified one joinpoint for the incidence series, resulting in two trends, the first with annual percent change of 34% and the second with 5.8%; for the mortality series no joinpoint was identified, and the annual percent change was 2.1%. CONCLUSION: There was a sharp increase in incidence rates during the study period, probably due to screening. Mortality rates had a small upward trend, and did not show major changes during the study period.